Evaluasi Pelaksanaan Sistem Pemberian Asuhan Keperawatan di Ruang Rawat Inap Terhadap Kinerja Perawat - Ibrahim Rahmat Antom Kurnia Mariyono Sedyowinarso (Fakultas Kedokteran Universitas Gadjah Mada, 2012)
Background: Nursing service is part of hospital service that supports the process of healing and recovery ofthe patient. Quality of nursing service reflects quality of service to patients. Model of Professional NursingPractice (MPNP) is a method to improve quality of nursing care. It is a system that includes structure, process,and professional values that enable professional nurses to manage nursing care. Performance of professionalnurses is reflected in behavior of nurses in managing patients. Presently nursing service has not met expectationof patients and their families. The practice of nursing service in most of hospitals in Indonesia has not reflectedthe practice of professional service. Some previous studies revealed that performance of nurses had not metthe standard, it mostly belonged to average. Therefore Grhasia Hospital implements 3 categories of service:service based on MPNP, toward MPNP and non MPNP which have not been evaluated.Objective: The objective of the study was to identify the difference in performance of nurses in providing mentalhealth nursing service in the ward with MPNP, toward MPNP, and non MPNP.Method: The study used cross sectional design and descriptive comparative approach, involving 31 nursesand 60 medical records at the ward of Class 1, L2 and L2A of Grhasia Hospital Yogyakarta. Data were obtainedthrough questionnaire and documentation study.Result: The result of the study showed compliance of nurses with nursing care standard of nurse performancein the ward with MPNP in average was 92.61%, toward MPNP in average was 77.64%, and non MPNP was inaverage 75.99%. Based on perception of nurses, performance in the ward with MPNP was in average 3.35, inthe ward toward MPNP was in average 2.85, and in the ward non MPNP was in average 2.81. The result ofstatistical analysis showed there was difference in performance between ward with MPNP, toward MPNP andnon MPNP in compliance with standard of nursing care with score of p=0,001 (p<0.05).Conclusion: Performance in the ward with MPNP was in good category, in the ward toward MPNP was also ingood category, whereas in the ward non MPNP was in average category, There was significant difference inperformance between the ward with MPNP, toward MPNP and non MPNP. The management of Grhasia Hospitalshould adopt MPNP of nursing care system in all the wards.Keywords: performance, model of professional nursing practice, nursing care system